2021
DOI: 10.1097/corr.0000000000002010
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Weightbearing Restrictions Are Associated with Worse Depressive Symptoms and Anxiety in Children Aged 5 to 7 Years with Perthes Disease

Abstract: Background Perthes disease most commonly affects children 5 to 7 years old, and nonoperative management, such as weightbearing and activity restrictions, is generally recommended. In earlier research in children aged 8 to 14 years who had Perthes disease, we found that the restrictions were associated with worse mobility, but mental health or social health measures were not linked. However, Perthes disease most commonly affects children 5 to 7 years old who are more emotionally and cognitively immature. Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…A study of prolonged non-weight-bearing for patients with severe hypoperfusion on MRI found that prolonged non-weight-bearing begun during early Legg-Calvé-Perthes disease decreased femoral head deformity 33 . Weight-bearing restrictions were not found to be associated with a meaningful increase in body mass index 34 , but were associated with increased depression and anxiety, in patients with Legg-Calvé-Perthes disease 35 .…”
Section: Legg-calvé-perthes Diseasementioning
confidence: 76%
“…A study of prolonged non-weight-bearing for patients with severe hypoperfusion on MRI found that prolonged non-weight-bearing begun during early Legg-Calvé-Perthes disease decreased femoral head deformity 33 . Weight-bearing restrictions were not found to be associated with a meaningful increase in body mass index 34 , but were associated with increased depression and anxiety, in patients with Legg-Calvé-Perthes disease 35 .…”
Section: Legg-calvé-perthes Diseasementioning
confidence: 76%
“…29 Our results are supported by similar findings in the literature evaluating PROMIS Anger and Anxiety domains in pediatric patients seen for other orthopaedic conditions. Do et al 30 used PROMIS domains, including Anxiety and Anger, to evaluate psychiatric symptoms in children aged 5-7 years with Legg-Calvé-Perthes disease. Similarly, Matsumoto et al 31 evaluated children (aged 4-18 years) with Perthes disease and found that the PROMIS domains they tested, which included Anger and Anxiety, exhibited both convergent and divergent validity.…”
Section: Discussionmentioning
confidence: 99%
“…11 A wide abduction brace treatment has been shown to produce good outcomes in hips with lateral pillars B and C in a large study by Rich and Schoenecker. 10 However, disadvantages of brace treatment include prolonged duration of treatment, activity restrictions, [11][12][13] and the need for patient adherence over a prolonged period.…”
mentioning
confidence: 99%